2019
DOI: 10.1097/bsd.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surgical Decompression on Functional Balance Testing in Patients With Cervical Spondylotic Myelopathy

Abstract: Study Design: A prospective cohort study. Objective: Quantify the extent of change in dynamic balance and stability in a group of patients with cervical spondylotic myelopathy (CSM) after cervical decompression surgery and to compare them with matched healthy controls. Summary of Background Data: CSM is a naturally progressive degenerative condition that commonly results in loss of fine motor control in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…In hereditary spastic paraplegia, a myelopathy resembling that in ALD, postural body sway was significantly higher than in healthy controls and was correlated with muscle strength in the legs (Marsden and Stevenson, 2013). In cervical spondylotic myelopathy, the most common myelopathy, postural body sway was also increased (Yoshikawa et al, 2008;Haddas et al, 2019b) and improved after decompressive surgery (Haddas et al, 2019a). Although these conditions do not have the same pathophysiology as ALD, they indicate that postural sway could be a useful way to measure myelopathy.…”
Section: Discussionmentioning
confidence: 96%
“…In hereditary spastic paraplegia, a myelopathy resembling that in ALD, postural body sway was significantly higher than in healthy controls and was correlated with muscle strength in the legs (Marsden and Stevenson, 2013). In cervical spondylotic myelopathy, the most common myelopathy, postural body sway was also increased (Yoshikawa et al, 2008;Haddas et al, 2019b) and improved after decompressive surgery (Haddas et al, 2019a). Although these conditions do not have the same pathophysiology as ALD, they indicate that postural sway could be a useful way to measure myelopathy.…”
Section: Discussionmentioning
confidence: 96%
“…We demonstrated that patients with CCM perceived greater bodily unsteadiness preoperatively as well as had worse objective assessments of postural instability, as reported previously. [19][20][21][22][23][24] In addition, decompressive surgery significantly improved both the subjective perceptions and objective assessments on instability. Furthermore, the present study potentially highlights several observations of surgical outcomes for postural instability in patients with CCM.…”
Section: Discussionmentioning
confidence: 96%
“…[20][21][22] Two recent studies addressed the surgical outcomes of postural instability in patients with CCM and drew similar conclusions. Haddas et al 24 examined 30 patients with CSM using a 3D motion capture system and demonstrated that surgical intervention resulted in improved standing balance postoperatively; however, the kinematic and spatiotemporal parameters did not completely reach the levels observed in asymptomatic controls. Similarly, Yano et al 23 examined 54 patients with cervical myelopathy using a stabilometer and demonstrated that postural stability was significantly regained during the postoperative period; but, it did not reach comparative levels seen in the healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…251 Surgical decompression normally enhances balance and gait, but the improvement may not be immediate. 252 In the chronic inflammatory demyelinating polyradiculoneuropathy, affecting both sensory and motor fibres and both distal and proximal nerve segments, body sway is much larger than in healthy subjects, and varies from a mainly ankle to a mainly hip strategy, 253 probably owing to the large extension of the sensory and motor impairment. The poor trunk control in these conditions resembles that observed in spinal cord injury, 254 where abnormal transmission of the somatosensory information to supra-spinal centres and of the descending commands to lower cord levels are accountable for ataxia.…”
Section: Other Neuropathies and Balancementioning
confidence: 99%